Recent advances in plant nanobionics and nanobiosensors for toxicology applications - Ansari, Mohammad Hasan Dad; Lavhale, Santosh; Kalunke, Raviraj M.; Srivastava, Prabhakar L.; Pandit, Vaibhav; Gade, Subodh; Yadav, Sanjay; Laux, Peter; Luch, Andreas; Gemmati, Donato; Zamboni, Paolo; Singh, Ajay Vikram (Current Nanoscience, 2020)
Emerging applications in the field of nanotechnology are able to solve a gamut of problems surrounding the applications of agroecosystems and food technology. Nano Engineered Material (NEM) based nanosensors are important tools for monitoring plant signaling pathways and metabolism that arc nondestructive, minimally invasive, and can provide real-time analysis of biotic and abiotic threats for better plant health. These sensors can measure chemical flux even at the single molecule level. Therefore, plant health could be monitored through nutrient management, disease assessment, plant hormones level, environmental pollution, etc. This review provides a comprehensive account of the current trends and practices for the proposed NEM related research and its (i) structural aspect, (ii) experimental design and performance as well as (iii) mechanisms of field application in agriculture and food system. This review also discusses the possibility of integration of data from NEM based nanosensors in current and emerging trends of precision agriculture, urban farming, and plant nanobionics to adopt a sustainable approach in agriculture,
Keywords: agro-ecosystems; engineered nanomaterials; nanobionics; Nanosensors; nanotechnology; nanotoxicology

Hybrid material for ferric ion detection & remediation: exceptional selectivity & adsorption capacity with biological applications - Yadav, Sanjay; Rajpurohit, Dushyantsingh; Dash, Soumya Ranjan; Bhojani, Gopal; Chatterjee, Shruti; Paital, Alok Ranjan (Microporous and Mesoporous Materials, 2022)
In this work, naphthalimide derived functionalized silica material SiO2@NAPIA (2,2'((((propylazanediyl)bis (methylene))bis(2,1-phenylene))bis(oxy))bis(N-(1,3-dioxo-1H-benzo[de]i soquinoline-2(3H)-yl)acetamide)) was constructed as a dual signaling and remediation material for ferric ions from a pool of 35 common ions (cations and anions) in the aqueous system. The material Cubic SiO2 shows a high surface area (1104 m2/g, pore volume (1.510 cm3/g), and pore diameter (6.3 nm) in the mesoporous range, which reduces further on functionalization to get the final material SiO2@NAPIA. The ferric ion selectivity through fluorescence quenching displays a SternVolmer quenching constant (Ksv) of 7.8 x 108 M-1 with a LOD (Limit of detection) value of 0.11 mu M for ferricion, which is 48 times lower than the USEPA (United States Environmental Protection Agency) maximum contaminant level (5.35 mu M) in drinking water. This material also shows a very high adsorption capacity (664 mg/g) for ferric ions fitting the Langmuir model isotherm with R2 = 0.99, which can be easily stripped out, and the material can be recycled. This material was also used as a sensory probe material for biosensing of ferric ions through fluorescence imaging in living organisms like Artemia salina and quantification in the real environmental sample. Furthermore, the antibacterial activity inspired by the ferric ion chelating affinity shows good potency against several Gram-negative and Gram-positive bacterial strains. The Minimum Inhibitory Concentration (MIC) & Minimal Bactericidal Concentration (MBC) of the material against these pathogens were found to be 100 & 200 mu g/mL respectively. This material signifies superior activity with respect to the ferric-ion selective materials known in the literature.
Keywords: Adsorption; Antibacterial; Biosensing; Functional material; Mesoporous silica; sensing